CATEGORY OF MEANING COMPONENTS IN ARABIC VERBS BEGINNING WITH THE LETTERS BA' : BINARY ANALYSIS - Muhammad Yunus Anis (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2021)
This study discusses the categorization of verbs based on the meaning components. To focus the discussion, the author only takes data on some verbs starting with the letter ba' in the Al Munawwir Arabic-Indonesian dictionary published in 2002. The research method is composed of three stages, the first stage is data collection using the observation, listening, and note-taking method. Meanwhile, data analysis uses the distributional method and binary analysis. The result of binary analysis shows that verbs starting with the letter ba' have the meaning of measure, action, and deed. Three verbs are composed of components meaning action and experience. Four verbs are composed of action and benefactive meaning components. One verb is composed of components meaning action and location. Fourteen verbs are indicated as human. The seven verbs are signaled as non-human. The six verbs can be indicated as human or non-human. Based on binary analysis, it can be concluded that verbs starting with the letter ba' are composed by meaning components in the form of process.